The Idea of Caliphate in the Context of the World War I: Dialogue and Confrontation between East and West - Svetlana A. Kirillina; Alexandra L. Safronova; Vladimir V. Orlov (RUDN Journal of World History, 2024)
The significance of the research topic is predetermined by the importance of Caliphatism as a phenomenon of social thought in the history of Islam. The purpose of this study is to analyze the regional specifics of the perception of the institution of Caliphal power in the center and on the periphery of the Islamic world during the First World War (1914-1918). The military failures of the Ottoman Empire and the triumph of the Western colonial powers forced Muslim thinkers to redefine the idea of the community ( ummah ) as a form of spiritual and political unification of the adherents of Islam. The authors focused on the ongoing discussions about the opportunities for Islamic unity and the prospects of the Caliphate in the changing conditions of world geopolitics. The original models of the “Arab Caliphate” and the “Ottoman Caliphate”, later opposed by the Caliphatists to the ideas of secular statehood, manifested themselves in the meaningful ideological dialogue between the defenders and opponents of the Ottoman government. Based on historical sources, the authors analyzed the intellectual work and political positions of Muhammad Rashid Rida (1865-1935), Ali Bash Hamba (1876-1918), Abdul Kalam Azad (1888-1958) and identified the eclectic nature of their ideological and political reactions to the weakening of the power of the Ottoman Sultan-Caliph. It is proved that the specific features of the traditional political culture of the Middle East, North Africa, and South Asia have become a decisive factor that led to a different interpretation of the tasks of the Caliphate in the main areas of Islam. In addition, the nature and mechanisms of the influence of the Ottoman intelligence services on the development of the philosophical and ideological justification of the Caliphal power among Muslim intellectuals have been clarified.